BLACK SOLDIER FLY (HERMETIA ILLUCENS) SEBAGAI MEDIA ALTERNATIF REDUKSI SAMPAH ORGANIK AMPAS TAHU - rahmawati, dwi ayu; Nilandita, Widya; Munfarina, Ida (ENVIROSAN : Jurnal Teknik Lingkungan, 2024)
Pollution can be caused by the disposal of industrial waste which is difficult to decompose and takes a long time. Biological conversion of organic waste with the Black Sodie Fry method is an alternative that can reduce industrial waste, especially fermented tofu and tofu dregs. BSF larvae have a protein fat percentage of 20-30% at 2030% compared to other microorganisms, which can be a source of nutrient-rich food. This study aims to determine the percentage of tofu dregs during fermentation and the ability of BSF to reduce tofu dregs. In this study, we used an experimental method that included two reactors, each containing 600 7 until 16 day old larvae. The frequency of feeding the larvae is 500 g for each larva every 3 days. The results showed that the reduction value of tofu and tofu in fermentation is 23.33% and 16.605%. The optimal reduction level of BSF larvae in tofu waste and tofu waste during fermentation was found in tofu waste, which reached 23.33%.